(3LeGdjGJ JbfjI GdGSJhOjh GdGaJQGVj aj GdEYdGf GdJdaRjhfjs - , (3GddGejs ((3YeGf(B:s (3OGQ CeLO ddfTQ hGdJhRjY(B,s, 2022)
(3LeGdjGJ JbfjI GdGSJhOjh GdGaJQGVj, JMOjO GdeUWdMGJ, eONd eaGgjej ddLeGd hGdJbfjI, YdGbI GdJbfjI HGdLeGd, GdJhXja GdLeGdj aj GdUhQI GdEYdGfjI, Cge GdYfGUQ GdJj JfgV HgG LeGdjGJ GdUhQI GdEYdGfjI, JhXja GdJbfjI GdMOjKI aj JUeje GdEYdGf GdJdaRjhfj, LeGdjGJ GdaVGA (B((3GdOjchQ(B)(3, GdaVGA hYdGbJg aj GdEYdGf GdJdaRjhfj, GdEYdGf GdJdaRjhfj, GSJNOGe GdCdhGf aj GdEYdGf GdJdaRjhfj, GdEVGAI hYdGbJgG HEfJGL GdGYdGf GdJdaRjhfj, GdGSJhOjh GdJdaRjhfj, GfhGY GSJhOjhgGJ GdJdjahjhf, GdehGUaGJ GdYGeI dJUeje GdCSJhOjh GdJdaRjhfj, GdOjchQ GdJdaRjhfj, GdecGf aj eQMdI GdJUhjQ, GdJWhQ GdJbfj aj aj GdGSJhOjh GdJdaRjhfj, Cge GdJbfjGJ GdMOjKI dYed GSJhOjh GaJQGVj, GdGSJhOjh GdGaJQGVj aj eLGd GdJdaRjhf, GdNdajGJ GdRQbGA hGdNVQGA (B((3GdcQheG(B)(3, GdWQb GdeNJdaI aj aUd GdcQheG, OhQ GdEVGAI YfO GSJNOGe GdcQheG, OhQ GdhSGFW GdeJYOOI aj JUeje GdGSJhOjh GdGaJQGVj, CgejI GdhSGFW GdeJYOOI aj JUeje GdEYdGf GdJdaRjhfj, GdJbfjGJ GdeSJMOKI HYO JWhQ GdceHjhJQ hHQGeL GdLQGajc GdeQJHWI HGdJMQjc, JUeje GdeLSeGJ KdGKjI GdCHYGO, GdLQGajc cCMO YfGUQ GdhSGFW GdeJYOOI aj JUeje GdEYdGf, GdNjGd GdYdej hGdJcfhdhLjG, GdNjGd hGdJNjd, GdEOQGc GdHUQj cLRA ef GdEOQGc GdMSj hJCKjQg Ydi EYdGfGJ GdJdaRjhf, GdEOQGc GdSeYj cLRA ef GdEOQGc GdMSj hJCKjQg Ydi EYdGfGJ GdJdaRjhf, GdeDKQGJ GdejcGfjcjI, GdeDKQGJ GdQbejI, eQGMd GfJGL (BVFX (3, GdeDKQGJ GdUhJjI, GdYhGed GdeDKQI aj eXGgQ GdLPH hGdEKGQI aj GdEYdGf GdJdaRjhfj, efgL GdHMK, eLJeY GdHMK hYjfJg, COhGJ GdHMK, UOb GdCOGI, NWhGJ GdJMdjd, GdLGfH GdJMdjdj, GdJbfjI GdQbejI GdeSJNOeI aj GdGSJhOjh GdGaJQGVj (B((3GdeDKQGJ GdUhQjI(B)(3, GdeDKQGJ GdQbejI (B((3GdHUQjI(B) (3aj GdGYdGf hJhXjagG ddOjchQ, GdHQGeL GdeSJNOeI aj JUeje GdEYdGf, OhQ GdGdhGf hGdGVGAI GdeSJNOeI aj JUeje GdEYdGf GdJdaRjhfj, OhQ GdNjGd hGdJQcjR heOi JCKjQg aj LeGdjI GdEYdGf(B. s
(3eQGLY U(B.201s
Keywords: (3GdEYdGf HGdJdaRjhfs; (3GdGSJhOjh GdGaJQGVjs